Role of Blockchain in the Internet-of-Things (Iot) - S A, Bragadeesh; Umamakeswari, A (International Journal of Engineering and Technology, 2018)
The proliferation of Internet of Things (IoT) has brought about a myriad of applications to life which range from smart homes, smart energy, smart buildings, smart cities to almost smart everything. This has been made possible by fully exploiting the services of cloud infrastructure, communication technologies, improved sensing devices and advancements in embedded devices which helps in incorporating intelligence even on tiniest of chips. Blockchain is a decentralised distributed approach that can facilitate management, control and also provide security. The application of blockchain is not restricted to cryptocurrency and security. It is perceived that Blockchain in Convergence with Artificial Intelligence, Cognitive Computing and Mobile Edge Computing can provide numerous prospects for framing solutions for IoT. Any application or system which deploys a IoT network can make use of Blockchain to achieve simplicity, transparency, security and cost efficiency. This paper tries to identify some key areas in which Blockchain can be used to exploit the IoT infrastructure and overcome the challenges faced. Few possible application domains in which blockchain can revolutionize the outcomes have been highlighted. A real-time case study in which Blockchain has been used to provide valuable benefits is discussed.Â Â